2001
DOI: 10.1177/14703203010020012201
|View full text |Cite
|
Sign up to set email alerts
|

Development of salt-sensitive hypertension in a sensory denervated model: the underlying mechanisms

Abstract: We use a novel salt-sensitive hypertensive model recently developed in our laboratory. This model shows that neonatal degeneration of capsaicin-sensitive sensory nerves renders a rat responsive to a salt load with a significant rise in blood pressure (BP). To test the hypothesis that development of salt-sensitive hypertension in sensory denervated rats is mediated by abnormal regulation of both circulating and tissue renin-angiotensin systems (RAS), neonatal Wistar rats were given capsaicin, 50 mg/kg s.c., on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
3
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 15 publications
1
3
0
Order By: Relevance
“…We have previously shown that development of saltsensitive hypertension induced by sensory denervation can be prevented by AT1 receptor antagonists [2,11]. Direct measurement of plasma renin activity and plasma aldosterone levels confirms that the circulating RAAS is insufficiently suppressed by high salt intake in this model, which may account, at least in part, for the increase in salt sensitivity.…”
Section: Discussionsupporting
confidence: 58%
“…We have previously shown that development of saltsensitive hypertension induced by sensory denervation can be prevented by AT1 receptor antagonists [2,11]. Direct measurement of plasma renin activity and plasma aldosterone levels confirms that the circulating RAAS is insufficiently suppressed by high salt intake in this model, which may account, at least in part, for the increase in salt sensitivity.…”
Section: Discussionsupporting
confidence: 58%
“…12,13 We showed that neonatal degeneration of capsaicin-sensitive sensory nerves increases blood pressure only when a high salt diet is given. 12,13 Moreover, we have shown that plasma renin activity is higher in sensory denervated rats than in sensory nerve-intact rats in response to a high salt intake, 14 indicating that plasma renin activity is insufficiently suppressed by salt load in the former one. Increased activity of the renin-angiotensin system may stimulate the ET system in this model.…”
Section: Discussionmentioning
confidence: 93%
“…12,13 Moreover, we have shown that plasma renin activity is higher in sensory denervated rats than in sensory nerve-intact rats in response to high salt intake, and that blockade of the AT1 receptors prevents the development of hypertension in this model. 13,14 Angiotensin (Ang II) has been shown to be a stimulus for ET-1 production both in vitro and in vivo. 15,16,17 It is likely that the activated renin-angiotensin system activates the ET system that in turn contributes the development of hypertension in this model.…”
mentioning
confidence: 99%
“…Moreover, this complex phenomenon of renin and aldosterone in SS or SR will go far toward identifying subjects who will be more susceptible to RAAS-blocking agents. 24…”
Section: Discussionmentioning
confidence: 99%